Hydrological Simulation Analysis for The Design of The Sei Busui Batuaji-Kuaro Bridge in East Kalimantan, Indonesia - Aco Wahyudi Efendi; Najla Ayu Febrina Nasution (Nusantara Civil Engineering Journal, 2026)
The Sei Busui Batuaji-Kuaro Bridge in East Kalimantan, Indonesia, is a critical infrastructure project requiring rigorous hydrological analysis to ensure resilience against extreme flood events. This study presents a comprehensive hydrological simulation to determine design flood discharges and maximum water levels (MWL) using rainfall data from 2016–2025. Rainfall frequency analysis employed the Log Pearson Type III distribution, validated with Chi-square and Smirnov-Kolmogorov tests. Flood discharges were estimated using five methods: Rational, Weduwen, Haspers, HSS-Gamma I, and HSS-Nakayasu. The HSS-Gamma I method was selected for its applicability to medium-sized catchments (127.58 km²), yielding a design discharge of 1,623.15 m³/s for a 75-year return period. Hydraulic analysis confirmed a freeboard of 1.693 m, exceeding safety standards. The findings emphasize the importance of region-specific hydrological methods and continuous monitoring to mitigate flood risks